Ultrastructure changes in the oocytes of caprine antral follicles - Sharma, R K; Chowdhury, S (The Indian Journal of Animal Sciences, 2012)
Ultrastructure analysis of the oocytes from medium antral follicles (MAF-3-5 mm diameter) and large antral follicles (LAF. >5 mm diameter) have been made during the follicular phase of goat (Capra hircus). The variations in the spatial distribution of cell organelles like mitochondria, microvilli. lipid droplet.s glycogen bodies and vocalization in the peripheral ooplasm of both the categories of oocytes revealed that as the oocytes advanced in size the spatial distribution of the organelles was altered and in large antral oocytes all the cell organelles were found concentrated near the zona pellucida. These ultrastructural variations within the oocytes of 2 categories shall be discussed in relation to their development. maturational and fertilizational competence.